Fifth Percentile Cutoff Values for Antipneumococcal Polysaccharide and Anti-Salmonella typhi Vi IgG Describe a Normal Polysaccharide Response - Schaballie, Heidi; Bosch, Barbara; Schrijvers, Rik; Proesmans, Marijke; De Boeck, Kris; Boon, Mieke Nelly; Vermeulen, François; Lorent, Natalie; Dillaerts, Doreen; Frans, Glynis; Moens, Leen; Derdelinckx, Inge; et al. (Frontiers in Immunology, 2017)
Background: Serotype-specific antibody responses to unconjugated pneumococcal polysaccharide vaccine (PPV) evaluated by a WHO standardized ELISA are the gold standard for diagnosis of specific polysaccharide antibody deficiency (SAD). The American Academy of Allergy, Asthma and Immunulogy (AAAAI) has proposed guidelines to interpret the PPV response measured by ELISA, but these are based on limited evidence. Additionally, ELISA is costly and labor-intensive. Measurement of antibody response to Salmonella typhi (S. typhi) Vi vaccine and serum allohaemagglutinins (AHA) have been suggested as alternatives. However, there are no large cohort studies and cut-off values are lacking. Objective: To establish cut-off values for anti-pneumococcal polysaccharide antibody response, anti-S. typhi Vi antibody and AHA. Methods: One-hundred healthy subjects (10-55 years) were vaccinated with PPV and S. typhi Vi vaccine. Blood samples were obtained prior to and 3-4 weeks after vaccination. Polysaccharide responses to 3 serotypes were measured by WHO ELISA and to 12 serotypes by an in-house bead-based multiplex assay. Anti-S. typhi Vi IgG were measured with a commercial ELISA kit. Allohaemagglutinins were measured by agglutination method. Results: Applying AAAAI criteria, 30% of healthy subjects had a SAD. Using serotype-specific 5th percentile (p5) cut-off values for post-vaccination IgG and fold increase pre- over post-vaccination, only 4% of subjects had SAD. One-sided 95% prediction intervals for anti-S. typhi Vi post-vaccination IgG (≥11.2 U/ml) and fold increase (≥2) were established. 8% had a response to S. typhi Vi vaccine below these cut-offs. AHA titer p5 cut-offs were 1/2 for anti-B and 1/4 for anti-A. Conclusion: We establish reference cut-off values for interpretation of PPV response measured by bead-based assay, cut-off values for S. typhi Vi vaccine responses and normal values for AHA. For the first time, the intra-individual consistency of all three methods is studied in a large cohort.